KEWENANGAN KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA PROVINSI BALI DALAM PEMBERIAN IZIN TINGGAL TERBATAS BAGI WARGA NEGARA ASING SEBAGAI SUBJEK HUKUM INTERNASIONAL - Roberta Kristine; Anak Agung Ngurah Yusa Darmadhi (Kertha Negara : Journal Ilmu Hukum, 2015)
The position of the individual as a citizen of a foreigner in a state is a subject of international law, which has the rights and obligations under the International law in a limited sense. Limited stay permit is valid residence permit granted to foreign nationals who meet immigration requirements. Each entry of foreigners into the territory of Indonesia, are entitled to the protection of both of the country of origin or destination country. However, each state has different procedures and processes in resolving acceptance influx of foreign nationals. This paper will discuss the limited stay permit of foreigners who stay in Indonesia.